THE RELATIONSHIP OF THE ROLE OF PARENTS WITH THE PRESCHOOL CHILDREN'S PSYCHOSOCIAL DEVELOPMENT IN MUSLIMAT NU KINDERGARTEN THORIQOTUL HIDAYAH CENTINI LAREN LAMONGAN - Yani Erniyawati; Sumarsono (Journal of Vocational Nursing)
Intoduction: Development experiences a rapid increase in the first five years of life, namely childhood which is referred to as the golden age or Golden Age. One of them is psychosocial development. In this phase, the child will go through a stage between initiative and guilt. Children try to get a feeling of initiative without having to feel guilty when they are going to do something. In psychosocial development, children have great responsibility in their daily activities and show a more mature level of being able to interact with others. The purpose of this study was to determine the relationship between the relation ship of the role of parents with the pre school children's psychosocial development. Methods: This research was quantitative with desaign study cross sectional with sample of 30 parents and 30 students, the sampling used was total sampling. Data collection using a questionnaire  a psychosocial development stimulation questionnaire and child development at the initiative versus guilt stage. The analysis used was Spearman's with significance level α <0.05. Results: The results showed that some or 15 (50%) of parents had an adequate role in the preschool children's psychosocial development, most or 17 (56.7%) children had sufficient psychosocial development. Spearman test results with significance level α <0.05 obtained α = 0.003, where α <0.05 means a significant relationship between the role of parents with the preschool children's psychosocial development in TK Muslimat NU Thoriqotul Hidayah Cetini Laren Lamongan. Conclusions: The role of parents is one important factor in the formation of children's psychosocial development. The role of parents is to provide stimulation that is to involve the child in simple daily activities at home. Further research is needed by using more objective measurement tools.